Ag-Introduced Antibacterial Ability and Corrosion Resistance for Bio-Mg Alloys - Shuai, Cijun (Biomed Res Int, 2018)
Bone implants are expected to possess antibacterial ability and favorable biodegradability. Ag possesses broad-spectrum antibacterial effects through destroying the respiration and substance transport of bacteria. In this study, Ag was introduced into Mg-3Zn-0.5Zr (ZK30) via selective laser melting technology. Results showed that ZK30-Ag exhibited a strong and stable antibacterial activity against the bacterium Escherichia coli. Moreover, the degradation resistance was enhanced due to the comprehensive effect of positive shifted corrosion potential (from -1.64 to -1.53 V) and grains refinement. The positive shifted corrosion potential reduced the severe galvanic corrosion by lowering the corrosion potential difference between the matrix and the second phase. Meanwhile, the introduction of Ag caused the grain refinement strengthening and precipitated-phase strengthening, resulting in improved compressive yield strength and hardness. Furthermore, ZK30-0.5Ag exhibited good biocompatibility. It was suggested that Ag-modified ZK30 was potential candidate for bone implants.